Relationship of early intensive- or coronary care unit admission and post-discharge performance of activities of daily living in patients with acute decompensated heart failure. (14th October 2021) - Kanda, M; Tateishi, K; Nakagomi, A; Iwahana, T; Okada, S; Kuwabara, H; Kobayashi, Y; Inoue, T
Abstract: Background: The management of acute decompensated heart failure (ADHF) often requires intensive care. However, the effects of early intensive care unit (ICU)/coronary care unit (CCU) admission on activities of daily living (ADL) in ADHF patients have not been precisely evaluated. Thus, we assessed whether early ICU entry can improve post-discharge ADL performance in these patients. Methods and results: ADHF patients (New York Heart Association I–III) admitted on emergency between April 1, 2014, and December 31, 2018, were selected from the Diagnosis Procedure Combination database and divided into ICU/CCU (ICU) and general ward (GW) groups according to the hospitalization type on admission day 1. The propensity score was calculated to create matched cohorts where treatment assignment (ICU/CCU admission) is independent of measured baseline confounding factors including ADL at admission. The primary outcome was post-ADL defined according to the Barthel index (BI) at discharge. Secondary outcomes included length of stay (LOS) and total hospitalization cost (expense). Overall, 12, 231 patients were eligible, and propensity score matching created 2, 985 pairs. After matching, post-ADL was significantly higher in the ICU group (GW 71.5±35.3 vs. ICU 78.2±31.2, P<0.001, difference in mean 6.7 (95% CI 5.1–8.4) points). After matching, LOS was significantly shorter and expenses were significantly higher in the ICU group. Subanalyses showed that patients with low ADL at admission (BI<60) mainly benefited from early ICU/CCU entry. Conclusions: Early ICU/CCU entry was beneficially associated with post-ADL in patients with emergency ADHF admission. ADL at admission might serve as a useful criterion for ICU admission. Funding Acknowledgement: Type of funding sources: None.